Evaluation of Violence Against Physicians: Sivas Province Example - Akgül, Gültekin; Yıldırım, Ali; Yücel Beyaztaş, Fatma (The Bulletin of Legal Medicine, 2024)
Objective: This research was planned to determine the frequency of physicians’ exposure to workplace violence, their reactions to violence, the causes of violence and solutions to violence. Methods: In this regard, the study group of the research consists of a total of 290 volunteer physicians. Data was collected using a survey consisting of 49 questions, including the sociodemographic characteristics of physicians, information about their working status, variables related to the violence that physicians were exposed to, and physicians’ thoughts about the causes, consequences and solution suggestions of violence. Results: The rate of physicians who were exposed to violence at least once in the working environment was 57.9%, physicians who were female, worked in internal branches, and had a career of 16 years or more were more likely to be exposed to violence, and 49.4% of physicians who were exposed to violence were more likely to be subjected to violence. It was concluded that he complained. It was determined that among the types of violence, psychological/verbal violence was the most common (82.1%), and the perpetrators of violence were mostly patients and their relatives. Conclusion: In order to prevent violent incidents and the negative effects of violence; Effective security measures should be taken, legal regulations should be made to deter acts of violence, the level of aware ness of violent incidents should be increased, healthcare workers should be given support and training on the effects of violence and coping with it, and the working conditions of physicians should be improved.